2011
DOI: 10.1007/s00101-011-1922-z
|View full text |Cite
|
Sign up to set email alerts
|

Anästhesie bei bariatrischer Chirurgie

Abstract: Today obesity is accepted as an independent disease. The WHO describes obesity as an epidemic disease occurring worldwide and associated comorbidities affect all organ systems. Bariatric operations lead to an improvement or even complete remission of obesity-correlated comorbidities. Bariatric operations are conducted as restrictive, malabsorptive, or mixed procedures. The preoperative anesthetic evaluation of comorbidities is carried out with a special focus on preexisting impairments of cardiac and lung func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
0
4
0
2
Order By: Relevance
“…Anesthesia for morbidly obese patients is generally regarded as being associated with increased risks [ 8 , 14 ]. Accordingly, there are various contributions on the anesthetic and perioperative management in this patient group [ 4 7 , 15 ]. They include the preoperative assessment, especially with regards to the airway management and monitoring strategies, the intra-operative phase, the emergence from anesthesia and the postoperative phase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anesthesia for morbidly obese patients is generally regarded as being associated with increased risks [ 8 , 14 ]. Accordingly, there are various contributions on the anesthetic and perioperative management in this patient group [ 4 7 , 15 ]. They include the preoperative assessment, especially with regards to the airway management and monitoring strategies, the intra-operative phase, the emergence from anesthesia and the postoperative phase.…”
Section: Discussionmentioning
confidence: 99%
“…Heinrich et al [ 10 ] reported, that approximately 20% of their patients received preoperative pulmonary function tests, which in return showed pathological values in over 90% of the cases. Such a streamlined approach is not always feasible, resulting in more generous recommendations for preoperative testing [ 4 , 6 ]. Overall, the reported incidences of comorbidities such as hypertension or diabetes mellitus are lower than maybe expected [ 9 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Die anatomischen Veränderungen der bariatrischen Chirurgie führen zu einem veränderten Hungergefühl sowie zu einem verringerten Magenvolumen und einer verringerten Resorptionsstrecke im Darm [5]. Nach Aufnahme von Nahrung kann unter anderem Übelkeit, Verstopfung, Erbrechen oder das Dumping-Syndrom auftreten [3,6].…”
Section: Introductionunclassified
“…Die bariatrische Chirurgie führt nicht nur zu Veränderungen bei der verzehrten Menge an einzelnen Lebensmitteln, sondern verringert auch Kalorienzufuhr im Allgemeinen [6,12]. Außerdem führen die niedrigere Nahrungszufuhr und das veränderte Essverhalten zu einer geringeren Aufnahme an Mikronährstoffen und Vitaminen, dass auch einen Mangel bis hin zur Anämie zur Folge haben kann [5,7]. Häufig tritt ein Mangel bei Eisen, Vitamin B 12 und Folsäure auf, aber auch von Kalzium, Vitamin D, Thiamin und weiteren Mikronährstoffen [7,9,10].…”
Section: Introductionunclassified